Aktivitas Antibakteri Ekstrak Etanol Daun Sungkai (Peronema canescens Jack) Terhadap 2 Jenis Bakteri Penyebab Jerawat dengan KLT-Bioautografi - Erliana, Dina; Nurhasana, Devi; Wiradimafan, Khafit; Avidlyandi, Avidlyandi; Yudha, Salprima; Adfa, Morina (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This research aims to examine the antibacterial activity of an ethanol extract of old sungkai leaves (DST) (Peronema canescens Jack) against the test bacteria Staphylococcus aureus and Staphylococcus epidermidis using the TLC-bioautography method. The concentration of the test extract was 15%, with the amount of extract spotting being 25 μL, and the eluent used was chloroform p.a. The results showed that the TLC chromatogram of DST ethanol extract showed 10 dense spots/spots, 6 spots of which could inhibit the growth of S. aureus (spots no. 2-7), and 7 of them (spots no. 1-7) could inhibit the growth of S. epidermidis. Spots with Rf = 0.06; 0.12; 0.27; 0.35 (spots no. 2-5) showed a larger clear zone than spots with Rf = 0.47 and 0.64 (spots no. 6-7) in inhibiting S. aureus. Meanwhile, spot number 1 (Rf = 0) showed the clearest zone among the other 6 spots in inhibiting S. epidermidis. In conclusion, the ethanol extract of old sungkai leaves (DST) has strong antibacterial properties against S. aureus and S. epidermidis. The results of this research have the potential to be developed to obtain potential candidate compounds as antibacterials from sungkai leaves. Keywords: Antibacterial, TLC-bioautography, Peronema canescens Jack, Staphylococcus aureus, Staphylococcus epidermidis